Foundations of educations - Tulio, Doris D. (Mandaluyong City : National Book Store, 2000)
Contents...Book 1. Psychology, anthropological, sociological... Book 2. Historical, Philosopical and legal
Includes references and index
Keywords: Educational psychology; Educational sociology; Educational anthropology